(3GdeONd ddYdhe GdbGfhfjI(B((3ehLR GdfXQjI GdYGeI ddbGfhf hGdfXQjI GdYGeI ddMb(B) /s - (3aQL, Jhajb MSfs ((3GdGScfOQjI(B: s (3eDSSI GdKbGaI GdLGeYjI(B, s)
(3aj fXQjI GdbGfhf,GdJYQja HGdbGfhf hNUGFUg hhVYg ef GdbhGYO GdGLJeGYjI GdCNQi hfWGbg,JbSje GdbGfhf(B((3CfhGY GdbhGYO GdbGfhfjI(B)(3,eUGOQ GdbGfhf,JWHjb GdbGfhf,GdJYQja HGdMb hCfhGY GdMbhb hJbSjeGJgG, CQcGf GdMbs
Keywords: (3GdbGfhfs